Characterization of barium titanate: BaTiO3 (BT) ceramics prepared from sol-gel derived BT powders - Deshpande, S. B.; Godbole, P. D.; Khollam, Y. B.; Potdar, H. S. (Journal of Electroceramics, 2005)
Sol-gel synthesis was attempted at room temperature by adding drop wise a clear solution (made by reacting BaCO3 with glacial acetic acid) to an equi-molar solution of titanium tetrabutoxide in isopropanol (IPA) and acetic acid. The gelation occurred within 30 minutes. The as-dried gel was calcined at 750 degrees C/6 h in air to obtain carbon free BaTiO3 powders. The resulting BT powders were further pressed into pellets and sintered at 1280 degrees C/4 h in air to get dense ceramics (density similar to 94%). XRD and SEM techniques were used for phase and microstructure analysis respectively. The room temperature relative permittivity (e) of 1280 increased to 7200 (at Curie temperature of 127 degrees C) at 1 kHz frequency. The dissipation factor (tan delta) similar to 1.6% was observed in these samples. Also, the ferroelectric properties such as spontaneous polarization (Ps similar to 13 mu C/cm(2)), coercive field (E-c similar to 4.0 kV/cm) and dielectric strength (similar to 34 kV/cm) are estimated for these samples. These performance parameters are compared with the available standard data from the literature.
Keywords: barium titanate; ferroelectricity; Microstructure; relative permittivity; sol-gel processing

Magnetic properties of nanosized ferrite powders synthesized by microwave-hydrothermal method - Khollam, Y. B.; Dhage, S. R.; Verma, S.; Potdar, H. S.; Deshpande, S. B.; Joy, Pattayil Alias; Date, Sadgopal K. (Ninth International Conference on Ferrites (ICF-9), 2005)
Nanosized powders of Fe3O4 and MgFe2O4 are synthesized by microwave-hydrothermal (MH) method. The ferrite powders thus obtained are characterized by powder X-ray diffraction, Mossbauer spectroscopy, scanning and transmission electron microscopies, vibrating sample magnetometer and AC magnetic susceptibility studies. Stoichiometric, nanosized (similar to 34 nm) Fe3O4 particles, having cubic symmetry with a(0) approximate to 8.39 angstrom, are obtained when molar ratio of Fe/NaOH used for the synthesis is 0.133. On the other hand, non-stoichiometric Fe3O4 is obtained when Fe/NaOH molar ratio is increased to 0.4. Though the powder XRD patterns of both stoichiometric and non-stoichiometric Fe3O4 are identical, Mossbauer spectroscopic studies showed different features in terms of asymmetry, intensity, isomer shift, etc. Saturation magnetization, M-s = 70 emu/g and coercivity, H-c = 178 Oe, at room temperature, are obtained for stoichiometric Fe3O4 powders. In the case of MgFe2O4, spherical, nanosized (similar to 3 nm) powders with cubic symmetry (a(0) approximate to 8.30 angstrom) and having very narrow size distribution are obtained under the MH conditions. The temperature and field dependent magnetic measurements on MgFe2O4 powders confirmed the existence of superparamagnetic state in this material with a superparamagnetic blocking temperature of 38 K below which typical magnetic hysteresis behaviour is observed.

Simple oxalate precursor route for the preparation of barium-strontium titanate: Ba1-xSrxTiO3 powders - Khollam, Y. B.; Deshpande, S. B.; Potdar, H. S.; Bhoraskar, S. V.; Sainkar, S. R.; Date, Sadgopal K. (Materials Characterization, 2005)
A simple one-step cation-exchange reaction between the stoichiometric solutions of ammonium titanyl oxalate (ATO) and barium hydroxide+strontium nitrate at room temperature (RT) is investigated successfully for the quantitative precipitation of barium-strontium titanyl oxalate (BSTO): Ba1-xSrxTiO(C2O4)(2).4H(2)O (x=0.25) precursor powders with nearly theoretical yield (greater than or equal to99%). The pyrolysis of BSTO at 730degreesC/4 h in air produced barium-strontium titanate (Ba1-xSrxTiO3; BST) powders. The characterization studies on BSTO and BST powders by using various physico-chemical techniques: micro- and chemical analysis, differential thermal analysis (DTA)/thermo-gavimetric analysis (TGA), XRD, FTIR, X-ray fluorescence (XRF) and scanning electron microscopy (SEM) revealed that the powders formed are cubic, highly pure, stoichiometric and sub-micron-sized with nearly uniform size and shape distribution. The ceramic compacts obtained by sintering the BST pellets at 1300degreesC/4 It showed density similar to95%, dielectric constant epsilon(Tc)similar to9500, tan delta-0.15% and T(C)similar to32 degreesC. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; permittivity; XRF

Synthesis and characterization of microwave-hydrothermally derived Ba1-xSrxTiO3 powders - Deshpande, S. B.; Khollam, Y. B.; Bhoraskar, Y. B.; Date, Sadgopal K.; Sainkara, S. R.; Potdar, H. S. (Materials Letters, 2005)
Submicron-sized, spherical, stoichiometric strontium substituted barium titanate: Ba0.75Sr0.25TiO3 (BST) powders are prepared by microwave-hydrothermal (MH) route under the MH conditions of 200 degreesC, 200 psi, and 30 min in strongly alkaline conditions (pH>12) using potassium titanyl oxalate (KTO) and nitrates of Ba and Sr as the starting precursors and KOH as the mineralizer. The characterization studies by XRD, XRF and SEM indicated that stoichiometric cubic BST powders (a(0)=3.992 A) were obtained by adjusting MH conditions mentioned earlier and keeping the (Ba+Sr)/Ti ratio in starting solution slightly in excess (similar to1.06). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; dissolution-recrystallization; Microstructure; microwave-hydrothermal synthesis; mineralizer; SEM; XRD; XRF

Synthesis of rutile from ATO and stearic acid - Patil, M. M.; Deshpande, V. V.; Deshpande, S. B.; Samuel, V.; Ravi, V. (Materials Letters, 2005)
Nanocrystalline titanium dioxide in the rutile phase has been obtained from the solid state reaction between ammonium titanyl oxalate (ATO) and stearic acid at 400 degrees C in air. The fine powders of ATO and stearic acid are mixed well using acetone in an agate mortar and pestle for 2 h. This mixture (weight ratio of ATO to stearic acid > 5) on heating at 400 degrees C produces rutile powders. For the ratios of ATO to stearic acid < 5, a mixture of anatase and rutile phases is obtained. Pure ATO yields anatase phase on decomposition at 400 degrees C. These powders were characterized by X-ray diffraction (XRD), BET surface area measurements and transmission electron microscopy (TEM) studies. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray techniques

Dielectric properties of BaTiO3 ceramics prepared from powders with bimodal distribution - Deshpande, S. B.; Potdar, H. S.; Patil, M. M.; Deshpande, V. V.; Khollam, Y. B. (Journal of Industrial and Engineering Chemistry, 2006)
BaTiO3 (BT) powders having bimodal distribution were synthesized successfully through a simple classical solid-state reaction route using cheap BaCO3 and TiO2 as starting materials. These powders were further processed in the form of green pellets to obtain dense BT ceramics having densities of similar to 94 similar to 96 % after sintering in air at 1350 and 1400 degrees C/4 h in air. The room temperature dielectric constant (epsilon(RT)) of similar to 1500 at 1 KHz frequency was increased to : 10000 at a Curie temperature (T-C) similar to 126 degrees C, showing a very sharp transition from a polar tetragonal to a non-polar cubic structure. The dielectric loss factor (tan 6) was similar to 1.5 %. SEM studies revealed the presence of dense microstructures having a distribution of smaller grains (size: 2 similar to 3 gm) surrounded by larger grains (>= 35 mu m). The ferroelectric hysteresis loop measurements on these samples gave values of spontaneous polarization (P-s) of similar to 12.0 mu C/cm(2), a coercive field (E-C) of similar to 2 similar to 2.5 kV/cm, and a dielectric strength (E-b) of similar to 48.0 kV/cm. DC-resistivity as high as 1.5 x 10(9) Omega-cm was obtained in these samples. All these results are quite comparable with reported ferroelectric/dielectric data and are discussed elaborately in this paper.
Keywords: BaTiO3; dielectric-ferroelectric properties; Microstructure; Sintering; stoichiometry

Room temperature synthesis of mesoporous aggregates of anatase TiO2 nanoparticles - Deshpande, S. B.; Potdar, H. S.; Khollam, Y. B.; Patil, K. R.; Pasricha, R.; Jacob, Nalini E. (Materials Chemistry and Physics, 2006)
The controlled hydrolysis reaction of titanium tetrabutoxide in presence of acetic acid in isopropanol, i.e. in non-aqueous media was adopted in the present work for the synthesis of nanocrystalline titania followed by aging at ambient conditions for longer duration. The powder XRD shows that the as-dried precursor (without any aging) is non-crystalline in nature. However, room temperature aging for longer duration > 120 days not only helped to develop crystallinity in TiO2 nanoparticles but also led to the formation of their self-assembly towards mesoporous aggregates creating sponge like TiO2 nano-structure having high surface area similar to 250m (2) g(-1)and narrow pore size distribution of 4-5 nm. TEM observations revealed the generation of spherical TiO2 nanoparticles (4-5 nm) assembled to form stable spongy scaffold having porous network structure with pore size 5-6 nm. Also, presence of a pronounced hysteresis loop in BET isotherm is indicative of a 3D-intersection network of the pores of size 4-5 nm. Further heat-treatment to the aged precursor at 400 degrees C/2 h in air modify pore network structure due to sintering of TiO2 particles as is observed in TEM studies and lowering thereby the surface area to 125 m(2) g(-1) (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Microstructure; porous materials; sol-gel processing; titania

Synthesis of star shaped Ba1-xSrTiO3 (BST) powders - Khollam, Y. B.; Potdar, H. S.; Deshpande, S. B.; Gaikwad, A. B. (Materials Chemistry and Physics, 2006)
Uniform star shaped strontium substituted barium titanyl oxalate Ba1-xSrxTiO(C2O4)(2) (BSTO)/strontium substituted barium titanate, Ba1-xSrxTiO3 (BST) powders were prepared via a simple chemical co-precipitation route with x = 0.15, 0.20, and 0.25. The process involved an addition of 0.1 M solution of titanium tetrabutoxide (BTM) in isopropanol (IPA) to 0.1 M oxalic acid in IPA containing 0.2 M of H2O to produce titanyl oxalate precipitate which was further reacted with 0.1 M solution of ammonium oxalate to obtain 0.1 M clear homogeneous solution of ammonium titanyl oxalate (ATO) with pH 4.25 containing titanium in the form of soluble anionic oxalate species [TiO(C2O4)(2)(2-)]. Stoichiometric quantities of barium hydroxide and strontium nitrate were dissolved in distilled water and its pH was adjusted nearly equal to that of ATO (similar to 4.15) by drop wise addition of dilute HNO3 solution 1:10 (v/v). The addition of this mixed cation precursor solution to ATO solution resulted in precipitation of strontium substituted barium titanyl oxalate (BSTO) having star shaped morphology. The calcination of BSTO precursors at 730 degrees C for 4 h in air produced cubic BST powders (a(o) similar to 4.001, 3.996 and 3.991 angstrom for x = 0. 15, 0.20, 0.25, respectively) having star shaped morphology. SEM, XRD and IFTIR techniques were used to characterize the BSTO/BST powders. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; capping agent; Co-precipitation; Morphology

Ferroelectric and ferromagnetic properties of (x)BaTiO3+(1-x)Ni0.94Co0.01Cu0.05Fe2O4 composite - Devan, R. S.; Deshpande, S. B.; Chougule, B. K. (Journal of Physics D-Applied Physics, 2007)
A group of elastically coupled ferroelectric and ferrite composites with the general formula (x) BaTiO3 + (1 - x) Ni0.94Co0.01Cu0.05Fe2O4 (where x = 0.85, 0.70 and 0.55) was prepared by the standard ceramic reaction method. The x-ray diffraction pattern of the composite reveals a spinel phase formation for the ferrite and perovskite phase formation for the ferroelectric phase without any other phase. The SEM micrographs were taken to determine the average grain size. The sintered composites exhibit typical hysteresis loops at room temperature. The effect of constituent phase variation on the hysteresis behaviour and the dielectric properties was examined. The parameters such as spontaneous polarization (P-s), breakdown voltage (E-b) and saturation magnetization (M-s) of the composites vary with the ferroelectric/ ferrite content. The temperature dependence of dielectric behaviour at a frequency of 1 kHz was also studied. With increasing content of BaTiO3, the dielectric constant increases and the Curie temperature decreases.

Synthesis of bismuth titanate (Bi4Ti3O12)powders via calcination of microwave-hydrothermally (MH) derived precursor - Khollam, Y. B.; Deshpande, S. B.; Samuel, V.; Potdar, H. S. (Indian Journal of Engineering and Materials Sciences, 2008)
Micrometer sized platelet-like particles of bismuth titanate (Bi4Ti3O12) ire prepared successfully by the calcination of a mixed-precursor in air. The mixed precursor is precipitated Under microwave-hydrothermal (MH) treatment via dissolution-recrystallization kinetics. The mixed precursor is precipitated in-situ by giving MH treatment (at 200 degrees C, 200 psi, and 30 min hold time) to the hydrolysed slurry containing Bi and Ti cations. The slurry was prepared by adding 20% aqueous KOH precipitant solution to a well-mixed stoichiometric nitrate solution containing Bi and Ti cations. XRD results revealed that the as-dried precursor consisted of a homogenous mixture of non-crystalline particles of Bi2O3 and TiO2. The calcination of the as-dried precursor at 700 degrees C/2 h in air resulted ill the formation of micron sized platelet like single-phase Bi4Ti3O12 powders having orthorhombic structure.
Keywords: Bi4Ti3O12; MH processing; SEM; XRD

Microwave-hydrothermal (MH) synthesis of Ba1-xSrxTiO3 (BST) - Deshpande, S. B.; Khollam, Y. B.; Potdar, H. S. (Ferroelectrics, 2011)
The barium-strontium titanate (BST) powders are used in fabrication of various microelectronic devices (because of their field- & composition dependent dielectric properties), integrated capacitors & as thin dielectric layer in DRAM (dynamic random access memories). The utility of MH synthesis route in deriving the BST powders was explored in the present studies under strongly alkaline conditions (pH > 12). Potassium titanyl oxalate (KTO) and nitrates of Ba & Sr were used as the starting precursors and KOH as a mineralizer. The typical BST composition, namely, BST with Sr = 0.25 was chosen for the experimentation. All the MH experiments were carried out in the MARS-5 microwave accelerated digestion system (CEM Corpn., USA). The stoichiometric BST powders were obtained under the MH conditions of 200 degrees C, 200 psi, and 30 min when the Ba/Sr ratio (greater than or similar to 3.25) was kept slightly in excess. The acetic acid treated and water washed MH derived powders showed formation of exclusively cubic BST phase (a(0) = 3.992 A degrees) as confirmed by XRD. These powders were further processed in the form of disks and sintered at high temperature (1350 degrees C/4 h) in air to obtain dense (rho >= 92%) ceramic bodies. Electrical measurements on the lapped and electroded samples (sintered at 1350 degrees C/4h) revealed epsilon(T-c) = 6800, tan delta = 0.1% and T-c = 32 degrees C. These properties are comparable to the reported standard data in the literature.